Nursing procedures: cardiovascular, respiratory & endocrine system handbook - Jamaludin, Thandar Soe @ Sumaiyah; Saidi, Sanisah; Mohd Mokhtar, Hanida Hani; Azmi, Junainah; Mohamed Zain, Siti Hajar (Kulliyyah Of Nursing, IIUM, 2025)
“Welcome to ‘Nursing Procedures: Cardiovascular, Respiratory, and Endocrine Systems,’ a comprehensive guide tailored specifically for Nursing students who are at undergraduates Nursing or Diploma Nursing students doing Adult Nursing. This book (manual) is meticulously designed to focus solely on nursing procedures pertinent to the cardiovascular, respiratory, and endocrine systems, offering concise, step-by-step instructions for essential clinical tasks. By honing in on practical procedures, this resource aims to equip students with the foundational skills necessary to provide effective patient care within these critical physiological domains. Each procedure is presented with clarity and precision, facilitating mastery and confidence in clinical practice. Whether in a classroom or clinical setting, this book serves as an invaluable companion, empowering students as they progress in their nursing journey.”